Ritual e performance feminina na Aldeia dos Orixás - Silva, Rosileide da (2018)
The present research proposes an analysis of the interrelations between the feminine and the Umbanda, from their performances and ritual practices, within the Terreiro Aldeia dos Orixás in Maceió / AL, of which I have been adept since 2011. There is a gap in academic production on the presence of women in Umbanda in Alagoas. Some studies in the State on women in Afro-Brazilian religions tend to emphasize roles and reproduce stereotypes such as the mother, the protector, or the seductive, sensual, dangerous, etc. In this sense, I seek to investigate the reality of the subjects in their ritual space from the field practice, evoking the meanings and meanings of these and the religious contexts in which the woman is inserted, to illustrate the construction of the otherness of the the subjects searched here. Afro-Brazilian religions became spaces of resistance, preservation, empowerment and liberation of black women, through knowledge, constituted and incorporated, valuing the knowledge framework of each one of them, as a repertoire for the formation of the community, respecting the ancestral knowledge. The Anthropology of Performance and Ritual, Visual Anthropology and Feminist Anthropology compose the main theoretical-methodological references to analyze the female protagonism observed by Ruth Landes (2002) in the candomblé terreiros in Salvador, the ritual concept of Victor Turner (2013), and still from the archival and repertory concepts of Diana Taylor (2013), in the development of the research on ritual and female performance addressing the presence and importance of women in the rituals practiced and in their elaboration; and how they see themselves as women and Umbandists regardless of the stereotypes attributed. Photoetnography will be used as methodological resources in order to capture the necessary images in order to contextualize my field of study. In this context, authors such as: Sylvia Caiuby Novaes (2005, 2017), André Alves (2004), Neusa Rolita Cavedon (2005), Boris Kossoy (1996) and Julice Salvagni (2013); and Autoethnography that together will be interfaces for a better understanding of the subjects. To do so, I will use Turner (1988) and Schechner (1988) to analyze the rituals and performances inserted in the context of practices in the Orixás Village. In Autoetnography, it is important to record that I work in the field research in roles that differ intrinsically in two fields that I consider complementary: I am cambona and researcher, which directly reflects on my relationship with the other adepts of the terreiro. Most of the bibliographies on Afro-Brazilian religions, and the women who compose them, were produced "from the outside" "inside" (MAGNANI, 2002). It is necessary that this look, and this knowledge, be determined from the inside out, and that women speak of themselves, that they construct their subjectivity from their place of speech.